Social capital and the impact of the recent economic crisis: Comparing the effects of economic and fiscal policy developments - Hörisch, Felix; Obert, Peter (Social policy and administration, 2020)
In this contribution, we offer an analysis that evaluates the impact of the recent financial and economic crisis on social capital. An economic crisis offers a unique chance to study people's associa...
Gesehen am 22.12.2020